A leptonic/hadronic jet model for the low-mass microquasar XTE J1118+480 - Vila, Gabriela Soledad (2011)
We present a one–zone jet model that fits the data from simultaneous broadband radio-to-X-rays observations of XTE J1118+480. We calculate the radiative contribution to the non-thermal spectrum of both relativistic electrons and protons, as well as that from secondary muons, charged pions and electron-positron pairs produced at high-energy hadronic interactions. The distributions in energy of all the particle species are obtained taking into account the energy losses, injection, decay and escape from the emission region. We also include absorption effects on the emission spectrum due to photon-photon annihilation. Finally, we discuss the detectability of XTE J1118+480 at high energies with the present instruments according to the predictions of our model for the gamma-ray band.